Amyotrophic lateral sclerosis and motor neuron syndromes in Asia. Issue 8 (19th April 2016) - Shahrizaila, N; Sobue, G; Kuwabara, S; Kim, S H; Birks, Carol; Fan, D S; Bae, J S; Hu, C J; Gourie-Devi, M; Noto, Y; Shibuya, K; Goh, K J; et al.
Abstract : While the past 2 decades have witnessed an increasing understanding of amyotrophic lateral sclerosis (ALS) arising from East Asia, particularly Japan, South Korea, Taiwan and China, knowledge of ALS throughout the whole of Asia remains limited. Asia represents >50% of the world population, making it host to the largest patient cohort of ALS. Furthermore, Asia represents a diverse population in terms of ethnic, social and cultural backgrounds. In this review, an overview is presented that covers what is currently known of ALS in Asia from basic epidemiology and genetic influences, through to disease characteristics including atypical phenotypes which manifest a predilection for Asians. With the recent establishment of the Pan-Asian Consortium for Treatment and Research in ALS to facilitate collaborations between clinicians and researchers across the region, it is anticipated that Asia and the Pacific will contribute to unravelling the uncertainties in ALS.